The spatial distribution of urban community gardens and their associated socio-economic status in Tehran, Iran - Asl, Sina Razzaghi; Azadgar, Anahita (Frontiers in Sustainable Food Systems, 2022)
Urban community gardens are a type of green space presenting a diverse role in urban systems. They can also be beneficial for solving the matter of food insecurity through providing self-sufficiency and resilience in low-income communities and increasing continuity of agricultural activities. Even though plenty of research has been conducted around community gardens, there is a noticeable research gap concerning case studies in different geographic contexts, especially in Middle East. This paper aims at mapping the spatial distribution of community gardens and their socio-economic attributes in Tehran, Iran. A methodology consisting of semi-structured interviews, qualitative and descriptive analysis along with tools such as ArcGIS were employed, and secondary data were obtained from various sources such as Tehran statistical yearbook of the year 2020. The results demonstrate that currently there are a total of 26 community gardens in Tehran and they run based on governmental funds and support with a strong educational motive backing them up. There is also an evident geographical distribution imbalance in terms of gardens placement with them mostly being present in the southern part of the city while in the northern districts the idea of community gardens has almost been nonexistent. Only districts 22, 8, and 7 among northern districts in Tehran have community gardens. In the southern part, district 19 includes the majority of gardens having 7 in total. In short, gardens are mainly placed in areas with lower average land prices, median household income, and higher education graduates.